Epigenetic priming by Dppa2 and 4 in pluripotency facilitates multi-lineage commitment - Eckersley-Maslin, Mélanie A. (Nat Struct Mol Biol, 2020)
How the epigenetic landscape is established in development is still being elucidated. Here, we uncover Developmental Pluripotency Associated 2 and 4 (Dppa2/4) as epigenetic priming factors that establish a permissive epigenetic landscape at a subset of developmentally important bivalent promoters characterised by low expression and poised RNA-polymerase. Differentiation assays reveal that Dppa2/4 double knockout mouse embryonic stem cells fail to exit pluripotency and differentiate efficiently. Dppa2/4 bind both H3K4me3-marked and bivalent gene promoters and associate with COMPASS and Polycomb bound chromatin. Comparing knockout and inducible knockdown systems we find that acute depletion of Dppa2/4 results in rapid loss of H3K4me3 from important bivalent genes whilst H3K27me3 is initially more stable but lost following extended culture. Consequently, upon Dppa2/4 depletion these promoters gain DNA methylation and are unable to be activated upon differentiation. Our findings uncover a novel epigenetic priming mechanism at developmental promoters, poising them for future lineage-specific activation.